The Effect of Mulligan Mobilization with Movement Modality on Improving Joint Flexibility in Gout Arthritis Patients - Septian, Deri; Buston, Erni; Efendi, Pauzan (Poltekkes Kemenkes Tanjung Karang, 2025)
Gout arthritis is a form of joint inflammation caused by the accumulation of monosodium urate crystals, leading to reduced joint flexibility, particularly in the knees. Non-pharmacological therapies such as the Mulligan Mobilization with Movement (MWM) technique provide a safe and effective alternative to enhance joint flexibility. However, the use of this therapy among patients with gout arthritis remains limited in primary healthcare settings. This study used a quasi-experimental design with 52 respondents divided into two groups: the intervention group (MWM) and the control group (Range of Motion exercises). Joint flexibility was measured before and after the intervention using a goniometer, and data were analyzed using statistical tests with a significance level of 0.05. The intervention group showed an increase in average joint flexibility from 123.85° to 140.19° (normal ≥140°), while the control group improved from 125.19° to 136.92°. The difference between the two groups was statistically significant (p=0.034), indicating that MWM therapy was more effective in improving joint flexibility than Range of Motion (ROM) exercises. The Mulligan Mobilization with Movement technique significantly improved joint flexibility in patients with gout arthritis and is recommended as a non-invasive rehabilitation method suitable for use in primary healthcare services.